PENGARUH PROPORSI KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL, LEVERAGE, DAN UKURAN PERUSAHAAN PADA PENGHINDARAN PAJAK - Carrica Wijayanti, Yoanis; Merkusiwati, Ni Ketut Lely A. (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
This study aims to obtain empirical evidence influence of proportion independent directors, institutional ownership, leverage, and the size of the company on tax avoidance. Measurement of tax evasion using the effective tax rate (ETR). Tax evasion is an action taken by the taxpayer to reduce the tax burden of companies that are legal. The role of government to carry out effective supervision is necessary for revenues from oil taxes can be optimized. Research conducted on all companies listed in Indonesia Stock Exchange 2011-2015 period. Sample selection is nonprobability sampling method purposive sampling technique. Total sample as many as 1,319 samples during the 5 period. Data analysis technique used multiple linear regression analysis. Results analysis showed the proportion of independent directors on the negative impact of tax avoidance. Institutional ownership has no effect on tax avoidance. Leverage a positive effect on tax avoidance. Company size has no effect on tax avoidance.
Keywords: Tax Avoidance, Propotion of Independent Commissioners, Institutional Ownership, Leverage, and Firm Size